PEMBELIAN KEMBALI SEBAGAI UPAYA PENYELESAIAN KREDIT BERMASALAH DAN PERLINDUNGAN HUKUMNYA BAGI BANK - Farida, Mutiara (Ensiklopedia Education Review, 2025)
Abstract : The Mortgage Loan Facility (KPR) provided by banks to debtors sometimes encounters issues during its course, which may be caused by debtor default. Therefore, the bank, as the creditor, needs legal protection. The purpose of this study is to examine how repurchase through the subrogation scheme can be undertaken by the bank as an effort to resolve non-performing loans and as a means of ensuring legal security for the bank itself. This study uses a normative legal approach, focusing on the analysis of applicable legal provisions. Based on the review of the Indonesian Civil Code and the Banking Law, it is shown that repurchase is chosen by the bank due to the absence of a registered Mortgage Certificate (Sertipikat Hak Tanggungan), which serves as the bank’s means of executing its rights over the collateral.Keywords: Default, Subrogation, Repurchase, Legal Protection.